Organized Labour: Market, Democracy and Globalization - Мария Маратовна Сакаева (Journal of Economic Sociology, 2010)
The author of this article presents a critical review of the monograph «Organized Labor in Postcommunist States: From Solidarity to Inﬁ rmity». The book, written by a famous researcher of labor movements P. Kubicek, includes the analysis of organized labor in Russia, Ukraine, Hungary, and Poland within postcommunist transformation. The book is written in a methodologically original way with a lot of data being used. The  author looked at organized labor within three dimensions: market, democracy and globalization. Comparative research is not conﬁ ned to four mentioned states, but also involves the comparison of labor movement in Western and Eastern Europe. In spite of interesting ﬁ ndings the study of organized labor in postcommunist states is mainly descriptive. The reasons and the results of declining of labor organizations are not thoroughly examined.